The Antioxidant Effect of Fermented Papaya Preparation in the Oral Cavity. (31st May 2015) - Fibach, E.; Ginsburg, I.
<x xml:space="preserve">Abstract</x> Oxidative stress has been recognized to play important roles in various diseases, including of the oral cavity. However, nutritional supplementation of antioxidants to ameliorate the consequences of oxidative stress is debatable. One caveat is that oxidative status is often measured under non‐physiological conditions. Here, we investigated the antioxidant potential of fermented papaya preparation (FPP), a product of yeast fermentation of Carica papaya Linn, under conditions that prevail in the oral cavity. Employing highly sensitive luminol‐dependent chemiluminescence assays, we show that its antioxidant capacity was augmented by saliva (up to 20‐fold, p < 0.0001, at 10 mg) and its components (mucin, albumin) as well as by red blood cells (RBC) and microorganisms present in the normal and pathological environment of the oral cavity. Polyphenols are major plant antioxidants. Using the Folin–Ciocalteu's assay, a very low amount of phenols was measured in FPP suspended in a salt solution. However, its suspension in saliva, albumin, mucin or RBC produced up to sixfold increase, p < 0.001, compared with the sum of polyphenols assayed separately. The results suggested that these enhancing effects were due to the solubilization of antioxidant polyphenols in FPP by saliva proteins and the binding to RBC and microorganisms, thus increasing their availability and activity. Copyright © 2015 John Wiley & Sons, Ltd.